MODIFIED RELEASE MULTI-UNIT SYSTEM: A REVIEW - RATHOD, JYOTI G.; DHOLE, SHASHIKANT N.; KULKARNI, NILESH S. (International Journal of Current Pharmaceutical Research, 2025)
Modified release multiunit dosage forms (MUFs) have emerged as a promising approach to achieve controlled and site-specific drug delivery with improved therapeutic outcomes. Pelletization, particularly via extrusion–spheronization, offers numerous formulation advantages, including uniform size, excellent flowability, and enhanced drug release control. This review provides a comprehensive overview of pelletization techniques with an emphasis on extrusion–spheronization, detailing its critical process parameters, formulation variables, and evaluation methods. Additionally, the classification of modified release systems and the comparative advantages of MUFs over single-unit systems are discussed. The integration of these technologies supports the development of patient-centric and robust drug delivery platforms with greater safety, efficacy, and compliance.